ANTIOXIDANTS IN DIETARY SUPPLEMENTS: EFFECTS ON OXIDATIVE STRESS AND AGING - Raimkulova K. A.; Rakhmonov F. Kh. (Web of Journals Publishing, 2025)
This article examines the role of antioxidants in dietary supplements, their impact on oxidative stress and aging processes. The mechanisms of action of antioxidants, their biochemical properties and potential for use in maintaining health and prolonging life are discussed.
Keywords: Antioxidants, oxidative stress, aging, dietary supplements, free radicals, mitochondria, polyphenols, coenzyme Q10.